2020
DOI: 10.1039/d0ma00520g
|View full text |Cite
|
Sign up to set email alerts
|

Tuning cesium–guanidinium in formamidinium tin triiodide perovskites with an ethylenediammonium additive for efficient and stable lead-free perovskite solar cells

Abstract: Utilizing cation tuning and implementing divalent cation hollowing and passivation to achieve efficient and stable pure Sn-based perovskite solar cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 47 publications
0
16
0
Order By: Relevance
“…The results also show a slight drop in the iodide concentration (I 3d, %) at 1−5% CsI. Tosado et al 36 and Hao et al 1 also reported about Sn 2+ oxidation in MASnI 3 , resulting in Sn 2+ and I − vacancies. As we know, the oxidation reaction of Sn 2+ to Sn 4+ produces two electrons (Sn 2+ ↔ Sn 4+ + 2e − ), and this reversible reaction is known as a self-doping process.…”
Section: ■ Methodsmentioning
confidence: 59%
See 1 more Smart Citation
“…The results also show a slight drop in the iodide concentration (I 3d, %) at 1−5% CsI. Tosado et al 36 and Hao et al 1 also reported about Sn 2+ oxidation in MASnI 3 , resulting in Sn 2+ and I − vacancies. As we know, the oxidation reaction of Sn 2+ to Sn 4+ produces two electrons (Sn 2+ ↔ Sn 4+ + 2e − ), and this reversible reaction is known as a self-doping process.…”
Section: ■ Methodsmentioning
confidence: 59%
“…As we know, the oxidation reaction of Sn 2+ to Sn 4+ produces two electrons (Sn 2+ ↔ Sn 4+ + 2e − ), and this reversible reaction is known as a self-doping process. 2,36 We suspect that Cs x FA 1−x SnI 3 can form in the Sn-enrichment condition because Cs + consumes electrons, which are produced from the Sn 2+ oxidation. Then, phase separation begins at 10% CsI, where the ratio of Sn 2+ −I increases again (Figure 3c and Table S1).…”
Section: ■ Methodsmentioning
confidence: 99%
“…[169] Tosado et al researched the impact of A-site cation www.advancedsciencenews.com mixing of FA by CsGA together with EDAI 2 on the stability of pure Sn PSCs. [122] To establish hydrogen bonding and alleviate local strains, they added Cs + and GA + cations into FASnI 3 crystal structure. GA + in FASnI 3 minimizes phase segregation due to the many hydrogen bonding sites, practically a good alternative for stabilizing mixed Sn-based perovskites.…”
Section: Improvement Of Film Quality and Defects Reductionmentioning
confidence: 99%
“…The stability of the devices was guaranteed over a long period (4000 h). The use of ethylenediammonium additive combined with Cs and GA doping of FASnI 3 induces passivation, which reduces defect density and allows fine control of film quality as well as stability 169 .…”
Section: Reducing Agentsmentioning
confidence: 99%